Antidepressant-like effects of water extract of Cordyceps militaris (Linn.) Link by modulation of ROCK2/PTEN/Akt signaling in an unpredictable chronic mild stress-induced animal model. (10th August 2021) - Lin, Yu-En; Chen, Yi-Chun; Lu, Kuan-Hung; Huang, Yun-Ju; Panyod, Suraphan; Liu, Wei-Ting; Yang, Shu-Hui; Lu, Yun-Sheng; Chen, Mei-Hsing; Sheen, Lee-Yan
Abstract: Ethnopharmacology relevance: Cordyceps militaris (Linn.) Link (CM) is a medicinal mushroom traditionally used in tonics for treating several neurological disorders, including epilepsy and anxiety, in Asia. Reports have shown that CM has anti-inflammatory and anti-oxidative effects and may be beneficial for depression management. Aim of the study: This study aimed to investigate the potential of CM as an antidepressant for a long-term unpredictable chronic mild stress (UCMS) rodent models and explore its underlying mechanisms. Materials and methods: Rats were orally administered with 125 (low, L), 250 (medium, M), and 500 (high, H) mg/kg bodyweight (bw) of the water extract of CM (WCM) for 35 consecutive days in the UCMS protocol. The levels of cerebral serotonin (5-HT), dopamine (DA), and metabolites in the frontal cortex of the rats were measured. Blood was collected to investigate the levels of proinflammatory cytokines, and the brain was dissected to assay the stress-associated ROCK2/PTEN/Akt signaling. Results: All doses of the WCM prevented abnormal behaviors induced by UCMS, including anhedonia and hypoactivity. The LWCM treatment reduced the turnover rate of 5-HT, and all doses of the WCM reduced the turnover rate of DA in the frontal cortex. The LWCM also attenuated the elevation of serum IL-1β induced by chronic stress. All doses of the WCM attenuated the ROCK2 protein hyperactivation, and the LWCM further increased the down-regulation of p-Akt/Akt signaling. Conclusion: The WCM has antidepressant-like effects, which may result from the regulation of the stress-related ROCK2/PTEN/Akt pathway. Therefore, the WCM may be developed and used for the complementary treatment of depression. Graphical abstract: Image 1 Highlights: Water extract of Cordyceps militaris (WCM) restored anhedonia induced by UCMS. WCM improved the total traveled distance and crossing events in the open field test. WCM normalized the upregulated turnover rate of monoamine induced by UCMS. WCM regulated the ROCK2/PTEN/Akt signaling in rat frontal cortex.